Importance of value based education on civilisational development - Berghout, Abdul Aziz; Ouahiba, Saoudi (Zes Rokman Resources, 2018)
This paper examines the importance of integrated value based education on civilisational development. It provides a framework for the study of education and its synthetic function on development of society. In very complex global environment, there is a need to re-visit the concept of education discerning its value and ethical aspect. Among others, the paper discusses: the concept of civilisation and civilisational development from an Islamic perspective as well as the importance of integrated civilisational education on sustainable civilisational development of societies. Along the various sections of the paper, the Islamic perspective is highlighted and further advanced. The paper explains the leading role of the Islamic view of development and civilisation on the progress of society. Furthermore, it proposes an integrated model of education that stresses the importance of aspects such as; wisdom, balance, respect, trustworthiness, integrity, trust, justice, peace, creativity, criticality and collectiveness and inclusiveness. The paper, follows textual analysis and library research to discuss the main aspects that make the general framework of development and civilisation from an Islamic perspective. The paper concludes that there is a need for an integrated Islamic model of civilisational development, in which value based education is central. This model should be: value loaded, balanced, comprehensiveness and flexible. Additionally, it has been clearly established that, inter alia, human factors, values, modern know how, technological means, managerial capabilities and governance are essential in the Islamic model of development. The paper also showed that civilisational education framework is essential in further studying the role of education on civilisational development.